Some Implications for Ērika: Implicatives in Danish, Finnish and Lithuanian - Holvoet, Axel; Spraunienė, Birutė; Laugalienė, Asta (Scandinavistica Vilnensis, 2019)
The article deals with implicative verbs, i.e., verbs that, both in their affirmative and negative forms, carry implications as to the factual status of their propositional complements, e.g. manage, forget, bother etc. Karttunen (1971), who introduced the notion, already pointed out that a verb that is implicative in one language need not necessarily have implicative counterparts in other languages. It is conceivable that some languages have semantic groups of implicatives not represented, or less well represented, in other languages, and this deserves to be investigated. In this article the authors offer just a very preliminary exploration based on three languages, one North Germanic, one Fennic, and one Baltic. They show that even such a small sample may reveal interesting differences. The authors also pause over certain general tendencies in the semantic development of implicatives. While most of the work on implicatives has been done in the tradition of formal semantics, the authors show that a more cognitively oriented approach (invoking mechanisms of subjectification) can yield valuable insights into the polysemy of implicatives.
Keywords: implicatives; presupposition; subjectification; Danish; Finnish; Lithuanian; lexical typology; semantics; cognitive linguistics